2015
DOI: 10.1016/j.cell.2015.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Rli1/ABCE1 Recycles Terminating Ribosomes and Controls Translation Reinitiation in 3′UTRs In Vivo

Abstract: To study the function of ABCE1/Rli1 in vivo, we used ribosome profiling and biochemistry to characterize its contribution to ribosome recycling. When Rli1 levels were diminished, 80S ribosomes accumulated both at stop codons and in the adjoining 3′UTRs of most messenger RNAs. Frequently these ribosomes reinitiated translation without the need for a canonical start codon, as small peptide products predicted by 3′UTR ribosome occupancy in all 3 reading frames were confirmed by Western analysis and mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
207
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(238 citation statements)
references
References 39 publications
(62 reference statements)
23
207
0
Order By: Relevance
“…Experiments without CHX, on the other hand, report positive correlations of varying magnitude (Fig 1D, 0x Gerashchenko NAR points and purple labels). Experiments by Pop [36], Lareau [26], Nedialkova [29], Guydosh [35] and Gardin [33] produce weak to moderate correlations, but experiments by Gerashchenko [34], Jan [41], Williams [42], Weinberg [38], and Young [37] produce fairly strong and highly statistically significant correlations.…”
Section: Pretreatment With Cycloheximide Consistently Changes Enrichmmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments without CHX, on the other hand, report positive correlations of varying magnitude (Fig 1D, 0x Gerashchenko NAR points and purple labels). Experiments by Pop [36], Lareau [26], Nedialkova [29], Guydosh [35] and Gardin [33] produce weak to moderate correlations, but experiments by Gerashchenko [34], Jan [41], Williams [42], Weinberg [38], and Young [37] produce fairly strong and highly statistically significant correlations.…”
Section: Pretreatment With Cycloheximide Consistently Changes Enrichmmentioning
confidence: 99%
“…An alternative experimental protocol uses an optimized harvesting and flash-freezing process that allows CHX pretreatment to be omitted [15,17,26,29,[33][34][35][36][37][38]. Experiments performed with this protocol have revealed that treatment with CHX affects several high-level characteristics of footprinting data, including the distribution of lengths of nuclease-protected fragments in mammalian cells [39] and the amount of enrichment in ribosome density at the 5' end of coding sequences in yeast [34].…”
Section: Introductionmentioning
confidence: 99%
“…ATP hydrolysis by Rli1 promotes release of the 60S subunit (Shoemaker and Green 2011). Depletion of Rli1 leads to aberrant reinitiation near the stop codon, leading to translation of 39 UTR sequences (Young et al 2015). In mammals, the protein Ligatin, or the complex of MCT-1 and DENR, promote release of mRNA and deacylated tRNA from the 40S subunit in the final step of recycling (Skabkin et al 2010).…”
Section: Termination and Recyclingmentioning
confidence: 99%
“…26,95 To get further insight into the involvement of ABCE1 in cell proliferation, we considered its potential role in the synthesis of proteins essential for cell cycle progression. The translation of certain transcripts is highly dependent on the initiation step, which is determined by both the activity of initiation factors and the 5 0 -UTR structure of mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Moreover, ABCE1 recycling activity may control non-canonical 3 0 -UTR translation on stalled ribosomes during stress. 26 The function of ABCE1 in ribosome recycling is conserved in archaea, in contrast to the initiation stage lacking the eukaryotic homologues of eIF3 and eIF5. 27 Thus, ABCE1 role in translation could be considered as a link between termination, recycling and initiation.…”
Section: Introductionmentioning
confidence: 99%